The Determinants of Self-Employment Growth: Insights From County-Level Data, 2000-2009. (February 2014) - Goetz, Stephan J.; Rupasingha, Anil
The sustained surge in self-employment since 2000 has largely gone unnoticed by policy makers and economic developers. Here the authors document this surge and identify variables associated with expanding self-employment. Results provide mixed evidence about the importance of capital access to self-employment growth, but reveal that different approaches are needed in different county types depending on their proximity to metro areas and population size, if the goal is to increase future rural self-employment rates. In all county types, the initial share of self-employed predicts self-employment growth, underscoring the importance of a culture favoring entrepreneurship and path dependence. Self-employment earnings and educational attainment also play significant roles, as does the ethnic diversity of the population. Population density matters in both rural and urban counties, but less so within individual rural–urban continuum code categories. State policy, especially labor market freedom, has important effects on self-employment in most county types and periods studied.